Liberdade de palavra: uma leitura ética do existencialismo sartreano - Corrêa, Kátia Marian (2016)
This paper seeks to elucidate the Sartrean existentialism from an ethical perspective, therefore using literature as an irreverent way relationship between the writer and the reader. There are several ways to explore the ethical aspect in the thinking of Jean-Paul Sartre, but in this work we see a more informative way to clarify it through literature. Since it already suggests a call between human freedoms through generous relationship between writer and reader, both require a compromise of freedom of each other and establish a trust between themselves. The responsibility and engagement between the writer and the reader are identified, and the role of the same plays to change a receptive world look for a transformer look, agent of practical actions and significant in the environment in which they are released, as Sartre puts. In order to talk on literature and freedom of speech, you must first resume some placements of Husserl on the design of intentionality, ie, "all consciousness is consciousness of something" and as near as the philosopher discusses the concept of meaning. While the significance is marked up while donor acts direction made by means of a language and therefore use of words, display objects in the world, men aiding in understanding the same. Soon after this resumption of phenomenology, shows the Sartrean reading of intentionality and later how Sartre addresses the issue of significance. Note that although some approaches of Husserlian theses in the Sartrean existentialism, the philosophy of Sartre, there is a change of perspective intend and mean a logical and epistemological aspect of Husserl, a world unveiling aspect in existential sense. In the latter, the main concern is about the human being, what it means to exist in the world, to be released along with others and how to carry the weight of an unconditional release, as well as a responsibility that is not only for their actions, but for all mankind. In addition to the issue of liability evidenced by Sartre in order to establish a dialogue and reflection on the subject, presents some placements to Levinas on the responsibility and the encounter with the Other. This is done because both philosophers were contemporaries within the phenomenology, and despite their differences of thoughts, both deal with themes that revolve around common issues that underlie the objective of this dissertation.